Epibiont relationships on hyolithids demonstrated by Ordovician trepostomes (Bryozoa) and Devonian tabulates (Anthozoa) - Galle, A; Parsley, R L (Bulletin of geosciences, 2005)
In Lower Paleozoic marine invertebrate communities of tabulate corals and trepostome bryozoans have been recognized as preferential epibionts on hyolithids. In the cases studied herein the data clearly indicates that epibionts prefer hyolithids to any other host. Several aspects of epibionts living on hyolithids are apparent: current-oriented hyoliths provide a desirable substrate and ease of feeding for them. That epibionts settle on the earliest juvenile portion of the hyolithid suggests that site selection is controlled by both composition of the juvenile periostracum and the position of the posterior dorsal conch. This is suggestive of a mutualistic relationship and possible co-evolution. The hyolithid keeps the epibiont in an optimum position for food, oxygen, and waste removal by facing into the current. The colonies on the dorsal and lateral sides of the conch provide added protection and additional mass for stability. This can be especially important in higher current regimes (hence more food, oxygen, and more efficient waste removal) or where the animal lives in habitats subject to disorienting currents.